Francis Mercury van Helmont's "Sketch of Christian Kabbalism" - Helmont, Franciscus Mercurius van, 1614-1699. (Aries Book Series, 2012)
Sheila A. Spector's translation of the Sketch of Christian Kabbalism, by Francis Mercury van Helmont (1614-98), is the first English version of the foundational seventeenth-century treatise appended to Knorr von Rosenroth's compendium, the Kabbala Denudata. After a survey of the historical context in general, Jewish and Christian Kabbalah in particular, and a brief biography of van Helmont, Spector's introduction explains how the author adapted the original Jewish myth for Christian purposes. The bilingual text contains a facsimile of the original Latin on one side, facing the English translation on the other, with Van Helmont's footnotes supplemented by the translator's endnotes. The edition is essential for scholars, though of interest to the general reader as well.